PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2007-2010) - Noerirawan, Moch. Ronni; Muid, Abdul (Diponegoro Journal of Accounting, 2012)
This study aimed to investigate the influence of internal and external factors on firm value in the study period of 2007-2010. In this study the internal factors that asset growth, funding decisions, and dividend policy. While external factors, namely firm inflation and interest rates. This study uses multiple regression analysis to test the hypothesis. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange. The sample in this study is determined by purposive sampling. Of the 128 companies, has acquired 32 companies that distribute dividends for 4 consecutive years. The results showed that the growth of assets and dividend policy have significant positive effect on firm value, the inflation rate is not significant positive effect on firm value, negatively affect funding decisions no significant effect on firm value, and the interest rate a significant negative effect on firm value.